Numerical Simulation of Static Ammonia Mixer in Denox Unit of Flue Gas Purification Plant - Anton L. Esipovich; Andrey V. Vorotyntsev; Andrey A. Roslyakov; Dmitry E. Sykhanov; Olga A. Demchenko; Anton V. Stepykin; Konstantin K. Shirshin (Energies)
The modeling of a mixer used for mixing ammonia and flue gasses is considered. Simulations were performed using Flow Vision 3.14 (TESIS LLC). As a result of the simulation, the distribution of concentrations along the mixer length was obtained at 50%, 65%, 85%, and full flue gas loading. It was found that operations at 100% and 85% gas loads are accompanied by an acceptable distribution of ammonia in the mixer volume (Cov = 0.05). The development and creation of an experimental model in real production was carried out according to the results of the numerical simulation. The simulation results were compared with experimental data on the speed and concentration of ammonia in the control section. The discrepancy, in general, did not exceed 15%. The developed mixer corresponds to modern developments in terms of mixing quality but is simpler in design and more compact.